Development and Validation of Kompetitive Allele-Specific PCR Assays for Erucic Acid Content in Indian Mustard [Brassica juncea (L.) Czern and Coss.] - Gill, Karanjot Singh; Kaur, Gurpreet; Kaur, Gurdeep; Kaur, Jasmeet; Kaur Sra, Simarjeet; Kaur, Kawalpreet; Gurpreet, Kaur; Sharma, Meha; Bansal, Mitaly; Chhuneja, Parveen; Banga, Surinder S. (Frontiers in Plant Science, 2021)
Brassica juncea L. is the most widely cultivated oilseed crop in Indian subcontinent. Its seeds contain oil with very high concentration of erucic acid (≈50%). Of late, there is increasing emphasis on the development of low erucic acid varieties because of reported association of the consumption of high erucic acid oil with cardiac lipidosis. Erucic acid is synthesized from oleic acid by an elongation process involving two cycles of four sequential steps. Of which, the first step is catalyzed by β-ketoacyl-CoA synthase (KCS) encoded by the fatty acid elongase 1 (FAE1) gene in Brassica. Mutations in the coding region of the FAE1 lead to the loss of KCS activity and consequently a drastic reduction of erucic acid in the seeds. Molecular markers have been developed on the basis of variation available in the coding or promoter region(s) of the FAE1. However, majority of these markers are not breeder friendly and are rarely used in the breeding programs. Present studies were planned to develop robust kompetitive allele-specific PCR (KASPar) assays with high throughput and economics of scale. We first cloned and sequenced FAE1.1 and FAE1.2 from high and low erucic acid (<2%) genotypes of B. juncea (AABB) and its progenitor species, B. rapa (AA) and B. nigra (BB). Sequence comparisons of FAE1.1 and FAE1.2 genes for low and high erucic acid genotypes revealed single nucleotide polymorphisms (SNPs) at 8 and 3 positions. Of these, three SNPs for FAE1.1 and one SNPs for FAE1.2 produced missense mutations, leading to amino acid modifications and inactivation of KCS enzyme. We used SNPs at positions 735 and 1,476 for genes FAE1.1 and FAE1.2, respectively, to develop KASPar assays. These markers were validated on a collection of diverse genotypes and a segregating backcross progeny. KASPar assays developed in this study will be useful for marker-assisted breeding, as these can track recessive alleles in their heterozygous state with high reproducibility.